2010
DOI: 10.2320/matertrans.mb200915
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Process of Disordering and Structural Refinement in Ni<SUB>3</SUB>Al during Severe Plastic Deformation by High-Pressure Torsion

Abstract: The process of grain refinement in Ni 3 Al by high-pressure torsion (HPT) was investigated up to 100 turns. The entire diametric sections of the deformed samples were analyzed by optical microscopy and image processing methods in order to evaluate both the spatial distribution and the volume fractions of the nanocrystalline and coarse grains. A thick band of nanocrystalline phase was formed in the middle section of the samples, and a structure containing mainly coarser ordered fragments was present in the vici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…The grain size of ~40 nm is much smaller than those of the HPT-processed pure metals 4,10,16,26 and many alloys 3,5,6,9 , but well comparable with those of HPT-processed intermetallics 39,40 , ceramics 21 , lattice softened alloys 8 and semi-metals such as Si 19 . The formation of nanograins can be attributed to two main reasons: first, the presence of a second phase blocks the dislocations motion and grain boundaries movement, and second, the in-situ formed intermetallics have strong covalent bonding.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The grain size of ~40 nm is much smaller than those of the HPT-processed pure metals 4,10,16,26 and many alloys 3,5,6,9 , but well comparable with those of HPT-processed intermetallics 39,40 , ceramics 21 , lattice softened alloys 8 and semi-metals such as Si 19 . The formation of nanograins can be attributed to two main reasons: first, the presence of a second phase blocks the dislocations motion and grain boundaries movement, and second, the in-situ formed intermetallics have strong covalent bonding.…”
Section: Resultsmentioning
confidence: 78%
“…For the latter, it was reported that the grain size in materials with covalent bonding is significantly reduced to the nanometer level by HPT 41 . The application of HPT to intermetallics as well as other materials with covalent bonding results in formation of a heterogeneous microstructure composed of nanograins and submicrometer grains 39,40 , whereas the grain size distribution is reasonably uniform after in situ production with HPT 33 . This is an important advantage of in-situ production of nanograined intermetallics by HPT.…”
Section: Resultsmentioning
confidence: 99%
“…However, the diffusive process cannot be observed in the short time window of classic MD. While in experiments, disordered nanotwins are observed after HPT [25][26][27]. There is no long-range ordered structure in the disordered twin.…”
Section: Fracture Mechanism Of Twin-free Ni 3 Almentioning
confidence: 99%
“…Therefore it seems to be possible in principle to prepare a real twinned Ni 3 Al structure. Recently, bulk nanostructured Ni 3 Al can be achieved via severe plastic deformation by high pressure torsion (HPT) [22][23][24][25][26][27]. In some cases, a large density of nanotwins are noticed by transmission electron microscopy in the nanocrystalline grains [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…It is applicable to hard and less ductile materials [5,6] even to intermetallics [7][8][9], ceramics [10][11][12][13], and semiconductors [14][15][16][17]. The samples for the HPT are used in the form of disk or ring and [18,19], because the shear strain is introduced in proportion to the distance from the rotation center [1], the ring sample is preferable to achieve a homogeneous structure throughout the sample [18,19].…”
Section: Introductionmentioning
confidence: 99%